The Tradition of the Angkola People on Slaughtering Buffaloes in the Death Ceremony - Arbanur Rasyid; Rayendriani Fahmei Lubis; Maulana Arafat Lubis; Nashran Azizan (Universitas Islam Negeri Ar-Raniry Banda Aceh, 2022)
This study aims to determine the background, process, and purpose of the Angkola people in slaughtering buffalo in a death ceremony. This study uses a descriptive analysis approach to describe the results of the research findings. In addition, the researcher used observation, interview, and document analysis techniques in collecting research data. The results indicate several reasons behind the slaughtering buffalo in the death ceremony. First, this tradition aims to preserve the Angkola cultural customs that have existed since Islam entered Indonesia. Besides, it also drives to keep the titles held by parents from being lost. Socially, this ritual is planned to feed the public where there are generally many people who come to see the procession. Lastly, Mora Kahanggi and Anak Boru played a significant role in supporting the funding for this ritual.